How is telegram virtual teaching assistant for math lessons? A Systematic Literature Review - Wahyuni, Ema Linda; Dewi, Aprianah Puspa Sari; Rizal, Moh.; Isnawan, Muhamad Galang; Fakhrurrozi , Imam (Nashir Al-Kutub Indonesia, 2024)
Telegram has significant potential as a virtual teaching tool in mathematics education due to its various advantages over other applications. This study aims to identify, review, and evaluate relevant research on the use of Telegram in mathematics learning, using the Systematic Literature Review (SLR) method. The process involves several stages: a) problem formulation, where the researchers define the problem to be explored in depth based on the selected topic, and b) applying the PRISMA approach for article screening. The initial search yielded 5,205 relevant articles. The findings indicate that Telegram users can leverage various advanced features to support their daily activities, including in education. One standout feature is Telegram BOT, which has been proven to effectively respond to user queries and commands, as shown in the study by Soeroso, Afrianto, Mayangsari, and Taali (2017). The implications of this research suggest that Telegram holds great potential as an interactive learning tool, particularly in supporting virtual mathematics instruction. Furthermore, Telegram's adaptability and ease of use make it an accessible option for teachers and students. Future studies are encouraged to explore its integration with other educational technologies to enhance learning outcomes.